Wire and Arc Additive Manufacturing of High-Strength Al–Zn–Mg Aluminum Alloy - Fang, Xuewei; Chen, Guopeng; Yang, Jiannan; Xie, Yang; Huang, Ke; Lu, Bingheng (Frontiers in Materials, 2021)
High strength 7xxx series aluminum alloys are of great importance for the aerospace industries. However, this type of aluminum alloys has poor processability for most additive manufacturing techniques. In this paper, a newly designed Al-Zn-Mg alloy was used as feeding wire to fabricate thin wall-shaped samples using wire and arc additive manufacturing (WAAM) technique. These samples were fabricated based on cold metal transfer (CMT) process with four different types of arc modes, i.e, CMT, CMT incorporated pulse (CMT+P), CMT incorporated polarity (CMT+A), CMT incorporated pulse and polarity (CMT+PA). The optical microscopy, X-Ray computed tomography, scanning electron microscope equipped with EDS and EBSD were employed to characterize the microstructure and phase constitution. The results clearly reveal that the porosity varies with the arc modes, and the densest sample with porosity of 0.97% was obtained using the CMT+P mode. The mechanical properties of the fabricated samples are also arc modes dependent. The tensile strength and yield strength of the sample manufactured by the CMT+PA arc mode are the highest. In terms of anisotropy, the strength differences in horizontal and vertical direction of the samples made by CMT+PA, CMT+A and CMT modes are all large, which is mainly ascribed to the pores distributed at the interlayer region.